Severe neuropathy due to inhalant abuse in adolescents from Pretoria - Clara M. Schutte; Jayendra Naidoo; Mandisa Kakaza; Manesh Pillay; Juliane Hiesgen (South African Family Practice, 2015)
Background: Inhalation of volatile agents, or solvent abuse, is a dangerous pastime practised by many young adolescents in various parts of the world. Benzine, a distillate of petroleum, is a cheap and readily available solvent that is often inhaled or “sniffed” to produce a short-lived feeling of euphoria or disorientation. The aim of this report is to describe four adolescents with severe polyneuropathies secondary to chronic benzine inhalation who were seen at the Steve Biko Academic Hospital in Pretoria’s Neurology Department.